Caracterização por ressonância magnética de alta resolução das compressões neurovasculares e das alterações estruturais do nervo trigêmeo em pacientes com neuralgia trigeminal primária - Leal, Paulo Roberto Lacerda (2015)
Neurovascular compression (NVC) is commonly accepted as being, in most patients, the main or most common cause of primary trigeminal neuralgia (TN), justifying microvascular decompression (MVD) as first neurosurgical option. In the same idea, other studies demonstrated that the degree of severity of NVC correlated with the long-term sucess rate after MVD. The chronic NVC may originate morphological changes in the trigeminal nerve (TGN), like nerve deviation, focal demyelination and atrophy. By contrast, little information is available about the real nature of the underlying nerve lesions of patients with TN. Objetive: The aim of this thesis was to study the characteristics by high-resolutionimaging (MRI) of NVC and structural alterations of TGN in patients with primary TN. Methods: On the First (MRI 1.5 Tesla [T]) and Second (MRI 3.0 T) Protocols, we studied, respectively, 100 and 40 patients, who underwent MVD for TN. All patients underwent a MRI with 3D T2-weighted, 3D time-of-flight (TOF) magnetic resonance angiography(MRA), and 3D T1-weighted Gadolinium-enhanced sequences in combination. Imaging analysis were performed to detect and to assess features of NVC and these data compared with the operative findings. On the Third Protocol, anatomical TGN parameters (volume, V; and cross-sectional área, CSA), obtained in 50 patients with primary TN and in 20 normal control subjects (control group), were compared between the symptomatic (ipsilateralTN group) and asymptomatic (contralateralTN group) sides of the face of patients and both sides of the control group. These data were correlated with patient’s characteristics, NVC characteristics and clinical outcomes at the 2-year follow-up after surgery. On the Fourth Protocol, the fraction of anisotropy (FA) and the apparent diffusion coefficient (ADC) ofTGN, in 10 patients with primary TN and in 6 normal control subjects, were obtained in a diffusion tensor imaging (DTI) sequencing, in a 3,0 T MRI, and compared between the ipsilateralTN, contralateralTN and control groups. Results: On the First Protocol, MRI sensitivity was 96.7% (88/91) and specificity 100% (9/9) for NVC detection. Image analysis correctly identified compressible vessel in 87.9% of cases and degree of compression in 84,6% of cases. On the Second Protocol, MRI sensitivity was 97.4% (37/38) and specificity 100% (2/2) for NVC detection. Image analysis correctly identified compressible vessel in 89.1% of cases and degree of compression in 83.8% of cases. On the Third Protocol, the mean V and CSA of the TGN on the ipsilateralTN group was significantly smaller (p<0.05) than those for the contralateralTN and control groups. On the ipsilateralTN group, the lowest values of V and CSA were found in TGN with NVC of grade III and in those of patients considered cured at 2-year of follow-up (p<0.05). On the Fourth Protocol, the FA of the ipsilateralTN group was significantly smaller (p<0.05) than those for the contralateralTN and control groups. The ADC of ipsilateralTN group was significantly higher (p<0.05) than those for the contralateralTN and control groups. Conclusion: 1.5 T or 3.0 T MRI using 3D T2- weighted in combination with 3D TOF-MRA and 3D T1-weighted Gadolinium-enhanced sequences proved to be reliable in detecting NVC and in predicting the degree of root compression. Results showed that atrophic changes, found in TGN of affected side of patients, were correlated with the severity of compression and clinical outcomes. Our work demonstrated also that DTI revealed alteration in FA and ADC values of affected TGN, and these alterations were correlated with atrophic changes in patients with TN caused by NVC